2022
DOI: 10.3390/foods11182740
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Polyphenols and Valorization of Fibers from Istrian-Grown Pomegranate (Punica granatum L.)

Abstract: Pomegranate fruit is an ancient fruit that is used not only because of its deep-red color and tasty arils but also due to the health benefits of its extracts. Pomegranate is a valuable source of bioactive compounds, including colorful anthocyanins and other polyphenols. The main objective of the present study was to gain comprehensive knowledge of the phenolic composition and antioxidative activity of a new pomegranate cultivar, grown in Northwest Istria, a part of the North Adriatic coastal area. Various part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Particularly, ellagitannins [ 43 ] and ANTO [ 44 ] have potent antiproliferative and pro-apoptotic activity against several cancer cells including those of the colon, breast, lung, cervix, prostate, liver, and oral/esophageal, to name a few. Although the extractive methodology and chromatographic conditions used in this study did not allow the identification of complex ellagitannins (e.g., punicalagin), as it has been reported for “Wonderful” and “Mollar de Elche” varieties by others [ 37 , 38 , 39 , 40 , 41 ] that the presence of ellagic acid and two of its glycosides in all three varieties of PMG (pink > red, white; Table S1 ) accounts for this. PMG´s ellagitannin-derived compounds (e.g., ellagic and gallagic acids, and urolithins A/B and B) not only have a high RSC but also antimutagenic activity [ 42 , 45 ].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Particularly, ellagitannins [ 43 ] and ANTO [ 44 ] have potent antiproliferative and pro-apoptotic activity against several cancer cells including those of the colon, breast, lung, cervix, prostate, liver, and oral/esophageal, to name a few. Although the extractive methodology and chromatographic conditions used in this study did not allow the identification of complex ellagitannins (e.g., punicalagin), as it has been reported for “Wonderful” and “Mollar de Elche” varieties by others [ 37 , 38 , 39 , 40 , 41 ] that the presence of ellagic acid and two of its glycosides in all three varieties of PMG (pink > red, white; Table S1 ) accounts for this. PMG´s ellagitannin-derived compounds (e.g., ellagic and gallagic acids, and urolithins A/B and B) not only have a high RSC but also antimutagenic activity [ 42 , 45 ].…”
Section: Resultsmentioning
confidence: 79%
“…It is noteworthy that the PC profile (molecular diversity and content) of PMGs depends on the fruit´s ripening stage, phenogenotype, pre/post-harvest conditions, and extractive solvent, among other factors [ 37 ]. Nevertheless, the flavonoid: total PC and ANTO: flavonoid ratios and ANTO fingerprint (cyanidin > delphinidin > pelargonidin, di > mono glucosides) are quite conserved among PMGs of different phenogenotypes and regions [ 8 , 37 , 38 , 39 , 40 , 41 ]. Also, while red PMG was a richer source of ANTO and organic acids, white and pink were richer in phenolic acids ( Table S1; see Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the content of polyphenols in PPE was 135.30 mg/g. Skrt et al 28 also used the ethanol solvent extraction method to extract polyphenols in pomegranate peel, and the yield of extracted polyphenols was 30.5 mg/g after optimizing the extraction conditions. This value was lower than the amount of extracted polyphenols in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, polyphenols have an important role as a part of the plant's defense mechanisms against different pathogens. Polyphenols are present in the human diet since they can be found in different fruits [12][13][14][15][16][17] and vegetables [18], medicinal plants [19][20][21][22] as well as other products such as vines [15] and bee products [21,[23][24][25]. Differences in the quantity of polyphenols and their bioavailability for humans depend on plant type, food product, etc.…”
Section: Polyphenols-chemical Characteristics and Divisionmentioning
confidence: 99%